The Influence of Leadership Behavior and Work Motivation on Performance of Physical Education’s Teachers in Manado City Indonesia - J. Podung, Beatrix; Tulian, Jeane; H. E. Sendouw, Recky (International Journal of Engineering and Technology, 2018)
This research was conducted with the aim to identify the influence of principal leadership behavior and teacher’s work motivation with the performance of physical education teachers of Junior High School in Manado City. The method used in this research is survey method with descriptive and associative approach. This research is intended to provide descriptive description of each variable and explain the pattern of relationship between one variable with another variable. The population is all teachers of physical education of public and private junior high schools in Manado City who are doing physical education teaching lessons in 2018. The population is 81 teachers of Physical Education. and the sample was obtained by using the formula of Taro Yamane with the sample size of (n) = 45 teachers of Physical Education. Sampling technique using simple random sampling. The questionnaire is compiled using the Likert scale. Further measurement results are analyzed by statistical correlation test and regression that preceded by testing requirements analysis. The conclusions of this research are (1) there is a positive correlation between principal leadership behavior with the performance of Physical Education teacher in Manado City; (2) there is a positive correlation between teacher’s work motivation and Physical Education teacher performance of Junior High School in Manado City; (3) there is a positive relationship of Principal leadership behavior and teacher work motivation with performance of Junior High School  Physical Education teacher in Manado City.